Pertanggungjawaban Notaris Terhadap Pembuatan Perjanjian Nominee Berdasarkan Putusan Pengadilan Negeri Gianyar Nomor : 259/Pdt.G/2020/Pn.Gin - Budiyanto, Budiyanto; Ismansyah, Ismansyah; Fendri, Azmi (LPPM Universitas Ekasakti Padang, 2023)
This study discusses the Gianyar District Court Decision No. 259/Pdt.G/2020/PN.Gin, which declared that Deed No. 10 and Deed No. 12, related to the purchase of land, constitute an unlawful act under Article 1365 of the Indonesian Civil Code. The focus of this research is: (1) How is the regulation of the creation of valid agreement deeds by a notary; (2) The notary's responsibility in the creation of nominee agreements; and (3) The judge's considerations in the court's decision regarding the nominee agreement. Using a normative juridical approach, this study utilizes both secondary and primary data. The results show that the notary has a significant responsibility to ensure that the deeds comply with the prevailing laws and regulations, and to prevent any coercion or fraud. Regarding the nominee agreement, the judge ruled that the agreement was made to circumvent the law, violating Articles 1337 and 1320 of the Indonesian Civil Code, as it does not meet the objective requirement of a valid agreement, namely